Synthesis and Characterization of a Magnetically Functionalized Silver-Curcumin-Chitosan Nanocomposite using Super Magnetite - Alzand, Hiba Ali; Al-Abodi, Entisar E. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Green synthesis of nanoparticles (NPs) has gained attention as an eco-friendly alternative to conventional methods, reducing toxicity to the environment and living organisms. This study aims to synthesize a novel nanocomposite (Mag-Chi-Cur-AgNPs) composed of silver NPs (AgNPs) prepared using curcumin (Cur) as a reducing and stabilizing agent, along with chitosan (Chit) and magnetic iron oxide (Mag). Cur-AgNPs were synthesized by dissolving Cur in dimethyl sulfoxide and deionized water, followed by the controlled addition of AgNO3. The solution was stirred, pH-adjusted, ultrasonicated, and incubated. Chit-Cur-Ag nanocomposite was formed by dissolving nanochitosan in acetic acid, mixing it with Cur-AgNPs, then stirring, washing, centrifuging, and drying. Finally, Mag-Chit-Cur-AgNPs were obtained by coating Chit-Cur-AgNPs with magnetic iron oxide. Characterization techniques confirmed the formation of the nanocomposite. The ultraviolet-visible spectrum is used to track synthesis stages and successful formation. Fourier transform infrared spectroscopy is used to identify bond peaks, verifying molecular changes, in the field. Emission scanning electron microscope analysis measured the nanocomposite size, with particles below 100 nm. X-ray diffraction is used to determine the crystalline structure and dimensions of each component. Magnetic properties were analyzed using a vibrating sample magnetometer, demonstrating high magnetic saturation. This study successfully synthesized and characterized Mag-Chi-Cur-AgNPs using green chemistry. The results confirmed the formation and stability of the nanocomposite, showcasing its potential for future biomedical and technological applications